Integrative Assessment of Pb and Cd Pollution in Porong Estuaries Using Sediment Chemistry, Bioavailability, and Bioconcentration Factor - Barlah Rumhayati; Catur Retnaningdyah (Indonesian Journal of Chemistry, 2018)
The aims of the research were to perform an integrative assessment of high metal pollution in Porong Estuary by determining (i) the distribution of heavy metals fraction in sediment, (ii) the potential risk of sediment to the metal bioavailability, and (iii) the bioaccumulation factor of heavy metals in benthic. Fractionation of heavy metals in the sediments was carried out by the European Community Bureau of Reference (BCR) sequential extraction method. The potential risk of sediment was determined from RAC (risk assessment code) value. Bioconcentration factor was determined based on the ratio of the concentration of heavy metals in benthic to the concentration of bioavailable metals from sediments. Heavy metal concentrations were measured using AAS. The results showed that non-resistant Pb and Cd was higher than resistant fractions. As a non-resistant fraction, Pb was found mostly as fraction 2, i.e., metal fraction adsorbed on the surface of the iron oxy/hydroxide sediment (34.5 ± 4.9%). Cd was more prevalent as fraction 3, i.e., an organic bound fraction (29.0 ± 1.8%). Furthermore, Porong Estuary sediments had medium risk for contributing the bioavailable Cd in the water bodies based on the RAC (15.6 ± 1.8%). Based on the bioconcentration factor, accumulation of Cd and Pb was low (48.00 ± 7.62% for BCF-Cd and 32.29 ± 6.90% for BCF-Pb). Based on the results above, it could be concluded that the Porong Estuary water bodies have not been polluted by Pb and Cd released from the aquatic sediment.